13th Floor Family Hub Strategy to Boost Weekend Occupancy and Attendance - Rahardja, Untung; Viktor A Sin, Muhamad (Pandawan, 2025)
The rising demand for family-friendly entertainment highlights a gap in the market for innovative, interactive recreational spaces. Many current hubs focus on traditional arcade games, overlooking immersive and diverse experiences for all age groups. Transforming the 13th floor into a family entertainment hub aims to address this gap. The main objective of the project is to repurpose the space into an interactive hub that boosts weekend occupancy, attracts local families and staycation guests, and creates a signature brand experience through unique, engaging features. This project employs market research, customer insights, and financial analysis to design the layout and entertainment zones. The strat- egy includes branding, interactive design, and diverse activity areas tailored to both children and adults. Development stages cover concept design to full-scale renovation, blending modern technology with traditional games to appeal to a wide audience. The expected outcomes include a 25% increase in weekend occupancy and a 30% rise in staycation bookings. The unique ”TIME-VERSE” branding is projected to generate 50% of brand awareness, while the variety of activities ensures appeal to families with different interests. Financial forecasts predict profitability with a break-even point within six months of launch. Ulti- mately, this transformation will fill a key gap in the local market by offering an engaging, memorable experience for families. With its strong financial potential and distinctive branding, the 13th-floor hub is positioned to become a premier destination for both local residents and tourists, enhancing the area’s reputation as a weekend getaway spot.